(untitled) (Heritage, 2024)
This study analyses the use of robotic combat systems during the Russian Federation’s invasion of Ukraine (special military operations of the armed forces of the Russian Federation) in two periods.The first period refers to the beginning of the special military operation (24 February2022) until the declaration of partial mobilization in the Russian Federation and the holding of referendums in four regions of Ukraine on joining the Russian Federation.The second period includes the conflict after the annexation of the Donetsk People’s Republic, Luhansk People’s Republic, Kherson, and Zaporizhzhiaregions to the Russian Federation. The study critically examines the concept of using unmanned aerial vehicles as well as the way of fighting against unmanned aerial vehicles in certain combat situations during a special military operation.This studyhypothesises that the success of using robotic combat systems depends on the experience in combating unmanned aircraft, the reliability of the command and information system, electronic warfare systems, and anti-aircraft defence systems.The side that planned a layered approach in combating drones (good intelligence assessment, use of electronic warfare systems, anti-aircraft defence systems, and efficient and effective application of lessons learned) had more success in suppressing the use of drones.